Degradation of Benzodiazepines after 120 Days of EMS Deployment. (3rd July 2014) - McMullan, Jason T.; Jones, Elizabeth; Barnhart, Bruce; Denninghoff, Kurt; Spaite, Daniel; Zaleski, Erin; Silbergleit, Robert; on behalf of the Neurological Emergencies Treatment Trials investigators
Abstract Introduction. EMS treatment of status epilepticus improves outcomes, but the benzodiazepine best suited for EMS use is unclear, given potential high environmental temperature exposures. Objective. To describe the degradation of diazepam, lorazepam, and midazolam as a function of temperature exposure and time over 120 days of storage on active EMS units. Methods. Study boxes containing vials of diazepam, lorazepam, and midazolam were distributed to 4 active EMS units in each of 2 EMS systems in the southwestern United States during May–August 2011. The boxes logged temperature every minute and were stored in EMS units per local agency policy. Two vials of each drug were removed from each box at 30-day intervals and underwent high-performance liquid chromatography to determine drug concentration. Concentration was analyzed as mean (and 95%CI) percent of initial labeled concentration as a function of time and mean kinetic temperature (MKT). Results. 192 samples were collected (2 samples of each drug from each of 4 units per city at 4 time-points). After 120 days, the mean relative concentration (95%CI) of diazepam was 97.0% (95.7–98.2%) and of midazolam was 99.0% (97.7–100.2%). Lorazepam experienced modest degradation by 60 days (95.6% [91.6–99.5%]) and substantial degradation at 90 days (90.3% [85.2-95.4%]) and 120 days (86.5% [80.7–92.3%]). Mean MKT was 31.6°C (95%CI 27.1–36.1). Increasing MKT was associated with greater degradation of lorazepam, but not midazolam or diazepam. Conclusions. Midazolam and diazepam experienced minimal degradation throughout 120 days of EMS deployment in high-heat environments. Lorazepam experienced significant degradation over 120 days and appeared especially sensitive to higher MKT exposure.